The Design of Citizen-Centric Green IS in Sustainable Smart Districts - Valerie Graf-Drasch; Robert Keller; Oliver Meindl; Felix Röhrich (Business & Information Systems Engineering, 2023)
Green information systems are often praised for their potential to foster sustainability in citizens' daily lives and meet their needs. With this focus on citizens, districts that use smart technologies provide a litmus test, the results of which will indicate how to design smart green information systems that better meet the needs and desires of citizens. To date, however, guidelines on how to design such green information systems in urban areas or actively involve citizens in this process are few and far between. In recognition and remedy of this shortage, the study draws on the design science research paradigm to develop seven design principles for citizen-centric green information systems that can be used in sustainable smart districts. These principles are evaluated in 15 semi-structured interviews and a prototype of a mobile district app for a citizen-centric green information system is instantiated. By taking this citizen-centric perspective, the paper fosters the active involvement of humans in the design of sustainable urban environments.
Keywords: 000; Sustainable smart districts; Smart cities; Green information systems; Sustainability; Citizen-centricity; Design principles